Negotiating Tradition and Aspiration: A Phenomenological Study of Rural Girls’ Pursuit of Higher Education in Bangladesh - Sajid, Abu Jonayed; Rabbi, Fazle; Islam, Hafizul (PT. Riset Press International, 2026)
This qualitative study explores how rural girls in Jamalpur District, Bangladesh, negotiate their pursuit of higher education within the intersecting forces of patriarchal norms, cultural expectations, and socioeconomic limitations. Drawing on Feminist Phenomenology and Bourdieu’s theory of habitus and cultural capital, the study examines twenty in-depth interviews to illuminate the lived meanings of aspiration, agency, and constraint. Using Braun and Clarke’s reflexive thematic analysis, five major themes emerged: conditional negotiation for family approval, balancing respectability with ambition, persistence amid economic hardship, emotional ambivalence, and education as empowerment. The findings reveal that girls’ educational journeys are shaped by moral expectations and relational negotiations rather than overt defiance. Their agency is expressed through strategic conformity, emotional endurance, and subtle acts of adaptation. Education, therefore, operates as both a site of constraint and transformation, allowing rural girls to reimagine womanhood within socially accepted boundaries. The study contributes to feminist educational discourse by foregrounding the emotional, cultural, and structural dimensions of gendered access to higher education. It calls for gender-transformative policies that address not only material barriers but also the cultural logics that define respectability and feminine virtue in rural Bangladesh.